PENGARUH SOCIAL MEDIA ENGAGEMENT DAN E-WOM TERHADAP MINAT DAFTAR MAHASISWA DALAM PROGRAM IISMA - Zahra Elvaretta Susilo; Devica, Sadana (Politeknik Ubaya, 2025)
This study aims to examine the influence of social media engagement and electronic word of mouth (e-WOM) on students’ interest in applying for the Indonesian International Student Mobility Awards (IISMA) program. Data were collected through questionnaires distributed to 152 student respondents aged under 18 to 24 years old. The data analysis used in this study includes validity testing, reliability testing with Cronbach’s Alpha, and multiple linear regression analysis to measure the influence between variables. Data were processed using confirmatory factor analysis (CFA) and regression analysis. Testing using the structural equation model (SEM) shows that students’ engagement with social media content, especially on Instagram, and the positive reviews they receive, have a positive impact on their interest in applying for the IISMA program. These findings suggest that an active, interactive, and informative communication strategy on social media can increase students’ interest in the program. Therefore, the IISMA program organizers are encouraged to develop more engaging content and expand their information outreach through social media platforms.